2015
DOI: 10.1098/rsif.2015.0590
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cortical bone adaptation to axial loading in the mouse tibia

Abstract: The development of predictive mathematical models can contribute to a deeper understanding of the specific stages of bone mechanobiology and the process by which bone adapts to mechanical forces. The objective of this work was to predict, with spatial accuracy, cortical bone adaptation to mechanical load, in order to better understand the mechanical cues that might be driving adaptation. The axial tibial loading model was used to trigger cortical bone adaptation in C57BL/6 mice and provide relevant biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 56 publications
(124 reference statements)
0
63
2
Order By: Relevance
“…Currently, the development of new treatments for diseases relies on preclinical interventions on cell cultures and animal models. A computational model of bone remodelling can be used to test novel interventions in silico and speed up the discovery-to-market time and reduce the cost of novel interventions (Pereira et al 2015;Schulte et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, the development of new treatments for diseases relies on preclinical interventions on cell cultures and animal models. A computational model of bone remodelling can be used to test novel interventions in silico and speed up the discovery-to-market time and reduce the cost of novel interventions (Pereira et al 2015;Schulte et al 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies on mouse models have demonstrated that the mechanical environment is a key determinant of bone remodelling in long bones and vertebrae (Birkhold et al 2017;Pereira et al 2015;Webster et al 2012). The form-function relationship where bone adapts its shape and material properties is referred to as Wolff's law (Wolff 1892), and many bone mechanistic mechanoregulation models in finite element analysis (FEA) have been developed to relate the mechanical stimuli to the bone adaptation (Cheong et al 2018a;Pereira et al 2015;Villette and Phillips 2017). Most of these algorithms are based on Frost's Mechanostat Theory, where bone apposition occurs above a higher, apposition limit and resorption occurs below a lower, resorption limit (Frost 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study internal changes in bone material properties in response to the mechanical environment is investigated. Although it has been shown that bone remodeling depends on the fluid velocity as well as the mechanical signals in the solid phase47 , only the latter one was used in this work and bone and other tissue types were modeled as isotropic elastic materials. The effect of using a poroelastic model during bone remodeling should be considered in the future.In nature and in this work, the end state of the healing phase serves as the initial condition of the remodeling phase.…”
mentioning
confidence: 99%